SCYL1 deficiency in CALFAN syndrome is associated with ER stress and cell death - Hellicar, John; Dattner, Tal; Sun, Tian; Percival, Lily; Chrisp, Ruby; Pietrobattista, Andrea; Witkos, Tomasz; Mironov, Aleksander; Leghlam, Lina; Jentsch, Carolin; Kölker, Stefan; Hoffmann, Georg F.; et al. (Disease models & mechanisms, 2025)
CALFAN syndrome is a rare genetic disorder affecting the nervous system and liver, with skeletal abnormalities also reported. It is caused by mutations in SCYL1, a gene encoding a ubiquitously expressed protein localized to the secretory pathway. SCYL1 interacts with trafficking components, including ARF GTPases and the COPI vesicle coat complex, and appears to function in retrograde secretory trafficking. Despite this knowledge, the mechanisms that underlie CALFAN pathology remain poorly understood. Here, using fibroblasts obtained from patients diagnosed with CALFAN syndrome and from SCYL1 knockout fibroblasts, we reveal an accumulation of the abundant secretory cargo procollagen type I in the endoplasmic reticulum (ER) upon SCYL1 deficiency. Surprisingly, we failed to observe procollagen-I-trafficking defects in the SCYL1-deficient cells. Nevertheless, ER accumulation of procollagen-I correlated with ER distension and induction of ER stress in the patient fibroblasts, which also underwent increased cell death. The phenotypes were observed at elevated temperatures, mimicking the induction of pathology under febrile conditions in patients with CALFAN syndrome. Our data suggest that ER stress induction is a pathological mechanism in CALFAN syndrome and that targeting this process may represent a therapeutic strategy.
Veröffentlicht: 27. November 2025
Gesehen am 19.02.2026